1979
DOI: 10.1007/bf00568199
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the antitussive effects of codeine phosphate 20 mg, dextromethorphan 30 mg and noscapine 30 mg using citric acid-induced cough in normal subjects

Abstract: 1. Protection by codeine 20 mg, dextromethorphan 30 mg, noscapine 30 mg, and placebo against citric acid-induced cough was determined in eighteen healthy subjects. 2. Drug differences occurred at 2 1/2 h following ingestion of the drugs but not at 1 1/4 h. 3. Only coideine 20 mg had a greater antitussive action than placebo, but dextromethorphan 30 mg also did not differ from codeine 20 mg. 4. This technique may offer a useful screening test for the activity of new potential antitussive compounds in man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 9 publications
0
35
0
Order By: Relevance
“…Previous studies on antitussives have been limited to a single dose response effort, e.g. cough threshold (Rees & Clark, 1983;Empey et al, 1979) and therefore do not fully characterise the subject's response. A few studies have counted coughs at different concentrations of irritant stimulus (Bickerman & Barach, 1954) but this takes no account of changes in cough intensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on antitussives have been limited to a single dose response effort, e.g. cough threshold (Rees & Clark, 1983;Empey et al, 1979) and therefore do not fully characterise the subject's response. A few studies have counted coughs at different concentrations of irritant stimulus (Bickerman & Barach, 1954) but this takes no account of changes in cough intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively cough may be induced by such agents as citric acid and again counted (Bickerman & Barach, 1954). The threshold for such cough production can be measured by administering increasing concentrations of citric acid (Empey et al, 1979). Attempts can be made to quantify the cough intensity by measuring noise (Gravenstein et al, 1954) or air flow rates (Bickerman et al, 1957).…”
Section: Introductionmentioning
confidence: 99%
“…In all studies except one, oral administration of dextromethorphan was associated with a significant reduction in cough challenge when compared with placebo. Empey et al (1979) studied 18 healthy volunteers to compare the antitussive effect of codeine (20 mg), dextromethorphan (30 mg), and noscapine (30 mg). Only codeine 20 mg had antitussive activity.…”
Section: B Dextromethorphanmentioning
confidence: 99%
“…In contrast, Dicpinigaitis et al (1997) observed significantly greater suppression of capsaicininduced cough 2 hours after ingestion of 30 mg of codeine compared with placebo. In citric acid-induced cough, 20 mg of codeine was associated with significantly greater cough suppression than placebo (Empey et al, 1979) In two exemplary studies investigating cough due to URTIs, Eccles et al (1992) found that codeine at an initial dose of 30 mg, followed by 4 days of dosing at 30 mg four times a day, had no effect greater than placebo syrup, either on objective initial cough recording or on subsequent self-reported cough. In the second study by the same group, oral codeine (50 mg) was compared with placebo syrup in 82 subjects in a parallel group design using three measures of cough assessment (Freestone et al, 1996).…”
Section: Opiates: Codeine and Morphinementioning
confidence: 99%
“…Noscapine, a phthalideisoquinoline alkaloid isolated from opium, has been widely used as an antitussive drug [1]. In recent years, noscapine has drawn more and more attention due to its excellent anticancer activity and low toxicity [2][3][4].…”
Section: Introductionmentioning
confidence: 99%